HIGH-RESOLUTION SPECTROSCOPY OF LONG-PERIODIC ECLIPSING BINARY ε AURIGAE - Golovin, Alex; Golovin, Alex; Kuznyetsova, Yuliana; Kuznyetsova, Yuliana; Andreev, Maxim; Andreev, Maxim (Одеські астрономічні публікації, 2007)
The results of spectroscopic observations of long-periodic eclipsing binary " Aur are reported. The observations were carried out during 2 nights in 2007 at 2-meter telescope located at the peak Terskol, Northern Caucasus (Russia). Here we present series of ε Aur spectra together with EW measurements of the most prominent absorption lines.